(untitled) (UNED Research Journal, 2018)
The Toa River basin is one of the main reserves for biodiversity and natural resources in Cuba. We studied the communal opinion about the extension programs designed to mitigate overexploitation currently affecting the basin. Our interviews and surveys found that there farmers and producers know little about forest extension methods, that current land use favors erosion, and that pollution originates in nearby towns and industries.